2016
DOI: 10.1002/jssc.201500845
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substituent position and cavity size of the regioisomers of monocarboxymethyl‐α‐, β‐, and γ‐cyclodextrins on the apparent stability constants of their complexes with both enantiomers of Tröger's base

Abstract: Enantiomers of Tröger's base were separated by capillary electrophoresis using 2(I) -O-, 3(I) -O-, and 6(I) -O-carboxymethyl-α-, β-, and γ-cyclodextrin and native α-, β-, and γ-cyclodextrin as chiral additives at 0-12 mmol/L for β-cyclodextrin and its derivatives and 0-50 mmol/L for α- and γ-cyclodextrins and their derivatives in a background electrolyte composed of sodium phosphate buffer at 20 mmol/L concentration and pH 2.5. Apparent stability constants of all cyclodextrin-Tröger's base complexes were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The separation efficiency can be increased at higher voltages, but this also increases the temperature difference in the middle and at the edge of the capillary, which leads to a decrease in efficiency. Based on our experience with a similar BGE [ 51 ], we have chosen a voltage (see Section 3.3 ) such that the current is around 50 μA. In addition to voltage, the current also depends on the ionic strength of the BGE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation efficiency can be increased at higher voltages, but this also increases the temperature difference in the middle and at the edge of the capillary, which leads to a decrease in efficiency. Based on our experience with a similar BGE [ 51 ], we have chosen a voltage (see Section 3.3 ) such that the current is around 50 μA. In addition to voltage, the current also depends on the ionic strength of the BGE.…”
Section: Resultsmentioning
confidence: 99%
“…The first optimization step was to select a suitable CD. Based on our previous experience with CDs [51], analyses were performed in the presence of CDs at a concentration of 10 mmol•L −1 , either in a 50 mmol•L −1 phosphate buffer at pH 2.5 (Figure 3) or in a 50 mmol•L −1 acetate buffer at pH 5 (Figure 4). From the measured electropherograms, it was concluded that the separation proceeds [46] were found in the urine of rats by GC-MS and LC-MS.…”
Section: Cyclodextrin Optimizationmentioning
confidence: 99%
“…[169] There are several available general methods for the synthesis of monosubstituted CD derivatives, which use selective deprotection of permethylated, perbenzylated or perbenzoylated CDs. The choice of the right position is crucial because, as has been shown, not only the size of the cavity, but also the position of the attached substituent has a great influence on a CD derivative's properties.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is attributed to the fact that analytes can interact and partially penetrate to both sides of the large γ‐CD cavity. The same research group has recently calculated the apparent stability constants of the complexes of the native α‐, β‐, γ‐CD, 2 I ‐O‐, 3 I ‐O‐, 6 I ‐O‐carboxymethyl‐α‐, β‐, γ‐CD with both enantiomers of Tröger's base in order to further evidence the effect of cavity size and the position of substitution in monocarboxymethyl α‐, β‐, and γ‐CDs . It was found that the cavity size plays an important role on the interactions that are developed, since the apparent stability constants were higher for CM‐β‐CD than for α‐ and γ‐derivatives.…”
Section: Chiral Selectorsmentioning
confidence: 99%